2018
DOI: 10.3892/br.2018.1179
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in cardiac PI3K/Akt/mTOR and ERK signaling pathways with the use of growth hormone and swimming, and the roles of miR21 and miR133

Abstract: Athletes misuse recombinant human growth hormone (r-hGH) to enhance their performance. Although r-hGH is known to increase cardiac hypertrophy, the underlying molecular mechanism remains unclear. The aim of the present study was to investigate the role of r-hGH in cardiac intracellular signaling pathways and of miR-21 and miR-133 expression in rat hearts during exercise. A total of 36 adult male Sprague-Dawley rats were divided into sedentary control (SC, n=9), swimming exercise (SE, n=8), r-hGH (GH, n=10) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In the present study, the expression of PI3K and Akt were increased by Ang II treatment, and this increased expression was reversed by lnc-FTX overexpression. Also, PTEN expression had the opposite effect to the expression of PI3K and Akt, which was consistent with the findings from a previously published study that showed that PTEN was a negative regulator of the PI3K/AKT signaling pathway [31]. The findings from the present study showed that lnc-FTX had a protective on hypertrophy of mouse cardiac myocytes induced by Ang II through inhibition of the PI3K/AKT signaling pathway by promoting the expression of PTEN and sponging miRNA-22.…”
supporting
confidence: 91%
“…In the present study, the expression of PI3K and Akt were increased by Ang II treatment, and this increased expression was reversed by lnc-FTX overexpression. Also, PTEN expression had the opposite effect to the expression of PI3K and Akt, which was consistent with the findings from a previously published study that showed that PTEN was a negative regulator of the PI3K/AKT signaling pathway [31]. The findings from the present study showed that lnc-FTX had a protective on hypertrophy of mouse cardiac myocytes induced by Ang II through inhibition of the PI3K/AKT signaling pathway by promoting the expression of PTEN and sponging miRNA-22.…”
supporting
confidence: 91%
“…Exercise-induced activation of PI3K/AKT/mTOR signaling and subsequent left ventricular physiological hypertrophy is not only mediated via disrupted miR-17 levels but also via other miR-clusters as shown in a rat model [63]: Ma et al found decreased miRNA-124 levels (targeting PI3K) and increased miRNAs-21, -144, and -145 (targeting PTEN and TSC-2), all leading to an induced activation of PI3K/Akt/mTOR signaling in cardiomyocytes. Furthermore swimming exercise and application of recombinant human growth hormone (r-hGH) in rats altered cardiac PI3K/Akt/mTOR signaling and miR-21 and miR-133 expression [96]. Reciprocal repression between miR-133 and calcineurin is involved in regulating cardiac hypertrophy [98].…”
Section: Micrornasmentioning
confidence: 99%
“…The GH-GHR axis induces chemoresistance in human MM by driving MITF-regulated and ABC-transporter-mediated drug clearance pathways [ 297 ]. Increased GH-JAK2-STAT3 signaling may thus explain the association between GH administration and MM ( Figure 2 ) [ 298 , 299 , 300 ]. Interestingly, the prepubertal somatotropic axis can be modified by milk consumption [ 301 , 302 ].…”
Section: Environmental Factors Upregulating Mir-21mentioning
confidence: 99%